2021
DOI: 10.1007/s42994-021-00047-0
|View full text |Cite
|
Sign up to set email alerts
|

Wheat speciation and adaptation: perspectives from reticulate evolution

Abstract: Reticulate evolution through the interchanging of genetic components across organisms can impact significantly on the fitness and adaptation of species. Bread wheat (Triticum aestivum subsp. aestivum) is one of the most important crops in the world. Allopolyploid speciation, frequent hybridization, extensive introgression, and occasional horizontal gene transfer (HGT) have been shaping a typical paradigm of reticulate evolution in bread wheat and its wild relatives, which is likely to have a substantial influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 180 publications
(190 reference statements)
0
10
0
Order By: Relevance
“…In contrast to rice and maize, hexaploid wheat emerged in a field of domesticated tetraploid wheat and interploidy hybrid swarms happened in the early agricultural field 61 . This complicated picture of the early domestication process 2 implying the contributions of interploidy and interspecific gene flow to the evolution of Triticum species might be underestimated previously. Recent evidence of pervasive introgression in wheat 3 , 5 also supported that the bread wheat utilized existing gene pool of tetraploid wheat through interploidy introgression during spreading 7 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to rice and maize, hexaploid wheat emerged in a field of domesticated tetraploid wheat and interploidy hybrid swarms happened in the early agricultural field 61 . This complicated picture of the early domestication process 2 implying the contributions of interploidy and interspecific gene flow to the evolution of Triticum species might be underestimated previously. Recent evidence of pervasive introgression in wheat 3 , 5 also supported that the bread wheat utilized existing gene pool of tetraploid wheat through interploidy introgression during spreading 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Genomic introgression, as a result of natural hybridization, is a creative evolutionary force in plants 1 . As one of the staple crops worldwide, the reticulate evolutionary nature of wheat has long been recognized, and pervasive introgressions have been reported among (sub-)species 2 . Recent studies showed that bread wheat received composite introgression from tetraploid relatives 3 5 , facilitating its adaptation to diverse environments and resistance to biotic stress 5 , by bringing allelic resources available 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fueled by the landmark bread wheat reference genome 12 , recent studies have reconstructed the phylogeny of Triticum-Aegilops species 13,14 , characterized the population structure of modern wheat 9,13,[15][16][17] , and identified historical gene flow from wild populations to bread wheat 13,14,16,18,19 . However, the population history of wheats (bread wheat and its wild relatives, or Triticum-Aegilops species) is largely incomplete, particularly the spatiotemporal dynamics of bread wheat emergence and dispersal, together with the genetic and ecological interaction between bread wheat and its wild relatives, remain elusive 6,20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…During the long course of evolution, plants have developed powerful adaptive mechanisms to cope with a variety of environments [ 1 , 2 ]. Flowering is an important stage in the process of plant life generation.…”
Section: Introductionmentioning
confidence: 99%